Automated immobilized metal affinity chromatography system for enrichment of Escherichia coli phosphoproteome. Issue 11 (8th May 2013) - Qu, Yi; Wu, Si; Zhao, Rui; Zink, Erika; Orton, Daniel J.; Moore, Ronald J.; Meng, Da; Clauss, Therese R. W.; Aldrich, Joshua T.; Lipton, Mary S.; Paša‐Tolić, Ljiljana
Abstract : Enrichment of bacterial phosphopeptides is an essential step prior to bottom‐up mass spectrometry‐based analysis of the phosphoproteome, which is fundamental to understanding the role of phosphoproteins in cell signaling and regulation of protein activity. We developed an automated immobilized metal affinity chromatography (IMAC) system to enrich strong cation exchange‐fractionated phosphopeptides from the soluble proteome of Escherichia coli MG1655 grown on minimal medium. Initial demonstration of the system resulted in identification of 75 phosphopeptides covering 52 phosphoproteins. Consistent with previous studies, many of these phosphoproteins are involved in the carbohydrate portion of central metabolism. The automated system utilizes a large capacity IMAC column that can effectively enrich phosphopeptides from a bacterial sample by increasing peptide loading and reducing the wash time. An additional benefit of the automated IMAC system is reduced labor and associated costs.